The Relationship between Physical Activity and Bone during Adolescence Differs according to Sex and Biological Maturity - Benjamin K. Weeks; Belinda R. Beck (Journal of Osteoporosis)
This study examines the relationships between bone mass, physical activity, and maturational status in healthy adolescent boys and girls. Methods. Ninety-nine early high-school (Year 9) students were recruited. Physical activity and other lifestyle habits were recorded via questionnaire. Anthropometrics, muscle power, calcaneal broadband ultrasound attenuation (BUA), bone mineral content (BMC), and lean tissue mass were measured. Maturity was determined by Tanner stage and estimated age of peak height velocity (APHV). Results. Boys had greater APHV, weight, height, muscle power, and dietary calcium than girls (𝑃<.05). Boys exhibited greater femoral neck BMC and trochanteric BMC while girls had higher BUA and spine BMAD (𝑃<.05). Physical activity and vertical jump predicted BMAD and BUA most strongly for boys whereas years from APHV were the strongest predictor for girls. Conclusion. Sex-specific relationships exist between physical activity, maturity and bone mass during adolescence.